Modernism in Africa - Pottgiesser, Uta; Tostões, Ana (De Gruyter, 2025)
Many African countries are home to extraordinary architecture that is virtually unknown. There are interpretations of Art Deco, International Style, Brutalism as well as of African vernacular architecture. Climate-responsive buildings with a fluidity of interior and exterior spaces play a large role. While many of these 20th century architects were of European origin, they were deeply influenced by their surroundings and found original, site-specific expressions, often in collaboration with African architects. A focus of the construction activities were educational buildings which played an important role for these young nations that mostly gained their independence in the 1960s. While some of the documented buildings have been restored, others are still awaiting reconstruction.